Estimation of the impact of an additional source of blood flow into the pulmonary artery in the early and late postoperative period after bidirectional cavopulmonary anastomosis - Fylypchuk, V. V.; Truba, Y. P.; Golovenko, O. S.; Prokopovych, L. M.; Boyko, S. M.; Dziurii, I. V.; Lazorishinetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The current work analyzes the results of the impact of an additional source of blood flow into the pulmonary artery to the outcome of the bidirectional cavopulmonary anastomosis, and the experience resulting from the improved pulmonary blood flow in patients after bidirectional cavopulmonary anastomosis (BCPA). During this work 66 patients were divided into two experimental groups: the first group consists of those patients with an additional source of pulmonary blood flow (ASPBF), the second group consists of patients without the ASPBF after BCPA. It was established that long–term results in the second group were better according to the following parameters: lower exudation frequency and lower pulmonary artery pressure, which resulted in a shorter period of hospital stay, better overall survival in the early and late postoperative periods, and better functional status of the cardiovascular system.